Pengaruh Trend Dan Promosi Terhadap Minat Beli Mahasiswa STIE IBMT Surabaya Di Aplikasi Tiktok - Grasela Abigail Giri; Is Fadhillah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research has the aim of wanting to find out more about " The Influence Of Trends And Promotions On The Buying Interest Of Stie Ibmt Surabaya Students In The Tiktok Application ". The background of this research is whether technological developments can increase a person's buying interest with trends and promotions on social media. This research is Descriptive Quantitative research using the survey method. The population in this study were 2019-2021 STIE IBMT Surabaya students who used the TikTok application. The number of samples studied by researchers was 51 respondents. The sampling technique used was purposive sampling. The data in this study were obtained using a questionnaire, and then analyzed using Multiple Liner Regression analysis with the help of the SPSS program. The results showed that trends and promotions have a significant effect on buying interest.